Respuesta :
Answer: x = 5t - a
Step-by-step explanation:
6x + a = 5 (x + t)
expanding the bracket
6x + a = 5x + 5t
collecting like terms
6x - 5x = 5t - a
x = 5t - a
Answer:
x = 5t - a
Step-by-step explanation:
in order to make x the subject of formulae from the expression 6x+a=5(x+t)
the first step to do is to open the bracket (BODMAS).
6x+a=5(x+t)
6x + a = 5x + 5t
collect the like terms
6x-5x = 5t - a
x = 5t - a
therefore the value of x in the expression , that is expressing x interms of t and a from the expression 6x+a=5(x+t) is solved to be x = 5t - a